Strategi Pengembangan Kawasan Minapolitan di Sumatera Barat Menggunakan Analytical Hierarchy Process - Viarani, Suci Oktri; Nesti, Lisa; Mufti, Wahyu Fitrianda (Politeknik ATI Padang, 2024)
West Sumatra Province has been designated by the Minister of Maritime Affairs and Fisheries as a Minapolitan area with seven regions in West Sumatra. Since the establishment of West Sumatra as a Minapolitan area, there has been no research examining the evaluation of suitability between planning and implementation of the Minapolitan fishing area development program in West Sumatra. The aim of this research is to determine a strategy for developing the Minapolitan area in West Sumatra which can improve the welfare of fishermen in the area. The data collection technique in this research is the primary data collection method in the form of field observations, interviews, FGDs and filling out questionnaires by respondents selected based on their knowledge of the Minapolitan area development program, such as representatives of the DKP, Port Service, business actors, and fishermen figures. The method used to determine strategic priorities for developing the Minapolitan area is using the Analytical Hierarchy Process approach. Based on the AHP calculation, the CR value <= 0.1 shows that respondents are consistent in making assessments and the resulting solutions are optimal. Likewise, for the CR value in the calculation for the assessment of each indicator, the CR value obtained is 0.0263 for the assessment of the supporting facility factor indicator, 0.0231 for the assessment of the supporting infrastructure factor indicator and 0.0061 for the assessment of the regional program factor indicator. The strategy obtained for developing the Minapolitan area is seen from the priority value between the highest factors, namely the supporting facilities and supporting infrastructure factors. The priority indicators that need to be immediately improved are the indicators for the availability of fishing ports, followed by the availability of fishing gear and the availability of clean water networks, the results obtained from the priority order of all the indicators assessed.